2011
DOI: 10.4490/algae.2011.26.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgal species composition and seasonal variation in biomass on Udo, Jeju Island, Korea

Abstract: Macroalgae are important primary producers in marine ecosystem. They don't only play an important role as bioindicators but also provide economic resources for humans. Seasonal and vertical variations in seaweed species composition and biomass were examined to determine the ecological status of seaweed beds around Udo, near Jeju Island. We obtained samples at two sites in the high-intertidal to subtidal zones using the quadrat method between June 2010 and May 2011. A total of 262 species were collected, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 23 publications
(32 reference statements)
1
17
0
1
Order By: Relevance
“…2). Moreover, these zonation patterns matched recent data from the Udo coast of Jeju Island (Kang et al 2011). The present results indicate that the vertical distribution of dominant species on Jeju Island have been maintained for the last 30 years.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…2). Moreover, these zonation patterns matched recent data from the Udo coast of Jeju Island (Kang et al 2011). The present results indicate that the vertical distribution of dominant species on Jeju Island have been maintained for the last 30 years.…”
Section: Resultssupporting
confidence: 67%
“…Although numerous studies have described these general zonation patterns, recent studies have suggested that these patterns may not be generalizable across geographic regions because peaks in abundance or diversity are not found consistently in particular depth strata (Balata and Piazzi 2008, Konar et al 2009, Heo et al 2011, Kang et al 2011. Therefore, there is great interest in investigating not only these exceptional patterns but also different zonation patterns in species composition, diversity, abundance, and community dynamics among areas at local scales (Konar et al 2009, Heo et al 2011, Kang et al 2011, Shin et al 2011.Macroalgal growth is influenced by multi-factorial in- This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…, (Oak et al, 2004;Ko et al, 2008;Kang et al, 2011). (van den Hoek, 1982), (Tenger and Dayton, 1987;Serisawa et al, 2004Serisawa et al, ).…”
Section: 군집지수mentioning
confidence: 99%
“…1960 153 (Kang, 1960), (Lee, 1974;Lee and Lee, 1976;Lee, 1976;Lee and Lee, 1982;Yoon, 1985;Boo, 1988;Kim, 1991;Kim et al, 2008) (Kim and Park, 1997) (Park et al, 1994) . , (Ko et al, 2008;Kang et al, 2011) .…”
Section: 서 론mentioning
confidence: 99%